Transformasi Digital Dalam Rantai Nilai Mobil Listrik: Tantangan dan Peluang Manajerial - Yudhistira Anugerah Pratama; Louisiani Mansoni Isnajati (Jurnal Ekonomi Manajemen Perbankan, 2025)
This study aims to explore the managerial challenges and opportunities in the digital transformation of electric vehicle value chain in Indonesia. An exploratory qualitative approach was employed to examine dynamics of digitalization from the perspectives of management, technology, and human resources. Findings reveal that most automotive companies face difficulties in fully integrating digital systems, mainly due to limited interoperability, lack of human resource readiness, and low digital literacy at the managerial level. Transformational leadership plays a crucial role in fostering an adaptive and collaborative work culture that supports digital innovation. Moreover, many companies have yet to embed digitalization into their long-term business strategies. Study recommends organizational restructuring, digital leadership training, and cross-sectoral collaboration as strategic solutions. These findings are expected to contribute to the development of relevant digital management models for the national electric vehicle industry.